Improved Mechanical Properties of Casting Made by New LPIC Technology - O. Vrátný; A. Herman; V. Novák; P. Chytka; M. Jarkovský; Z. Kopanica; J. Zeman (Archives of Foundry Engineering, 2024)
Nowadays, the emphasis is on improving the integrity of precision castings of Fe, Ni and Co alloys (improving the mechanical properties of the material and increasing process efficiency) more than ever before. For this reason, a technology has been developed which is a combination of low-pressure casting and investment casting. The premise of the combination of these technologies is that a high degree of automation should be achieved, based on low-pressure casting, while bottom filling will reduce reoxidation phenomena during filling. Mainly due to the higher purity of the melt, higher values of mechanical properties in conjunction with shape and geometric accuracy are expected, which guarantees the investment casting. For this purpose, an experimental casting machine has been designed, which is a combination of these two technologies, where we are able to eliminate the disadvantages of low-pressure casting, which include, for example, the low variability of the usable materials, as well as the disadvantages of investment casting, which include the low automation of the process. Using an experimental machine, tensile and impact test samples were cast and subsequently tested. From the initial experiments, it can be said that using this technology we are able to cast materials based on Fe alloys, Ni alloys and Co alloys with mechanical property values that are even close to or within the range of mechanical properties of the formed materials. As a result, the mechanical properties of castings cast by the LPIC method are shown to be tougher and stronger.